ANALISIS YURIDIS PERTANGGUNGJAWABAN PIDANA PEMBUAT STEMPEL YANG DIPERGUNAKAN KONSUMEN UNTUK TINDAK PIDANA DIKAITKAN DENGAN AJARAN KAUSALITAS - Putri Fauziah; Erdianto Erdianto; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In the Penal Code (Penal Code) article 263 governs the crime of mail forgery. There are several actions that belong to the type of mail forgery, one of which is the creation of stamps that can cause the stamp maker to also be held accountable. But in reality, the stamp was only used as a means of evidence in the trial. This is known from the example of the Case Verdict Number: 1293/Pid.B/2018/PN. Pekanbaru with defendant Agus Salim Ahim, Number:325/Pid.B/2013/PN. Pekanbaru with defendant Masrizal, and Number: 423/Pid.B/2017/PN. Pekanbaru with defendant Madi Permana Sesa states that the stamp is only used as a tool of evidence seized for destruction. Criminal liability is often also associated with the doctrine of causality. Causality is used as a